The Bulgarians and the Arab siege of Constantinople in 717–718 - Cecota, Błażej (Balcanica Posnaniensia. Acta et studia, 2011)
The article is devoted to the role of the Bulgarians during the Arab siege of Constantinople in 717–718, regarded as one of the key events that halted the expansion of Islam into Europe. The author analyzes the political and military significance of the participation of the Bulgarians under Khan Tervel, as well as the controversies present in Byzantine and Arab sources. The aim of the article is to reinterpret the problems connected with Bulgarian participation in the events of 717–718 and to clarify the existing historiographical disputes. The author employs a comparative analysis of Byzantine and Arab sources together with a critique of earlier interpretations. The article demonstrates that the Bulgarians had already played an active role in Byzantine politics before the siege, intervening in struggles for the imperial throne and maintaining strong influence in the southern Balkans. The author also emphasizes the significance of Leo III’s contacts with the Arabs and suggests that the events surrounding Amorium during the Abbasid campaign against Byzantium may have influenced the Bulgarian decision to intervene. The results of the analysis indicate that the participation of the Bulgarians in repelling the Arabs constituted an important element of the defense of the empire, although the available sources do not allow for an unequivocal reconstruction of the course of events.